Current Management of Left Ventricular Assist Device Erosion. Issue 6 (4th September 2013) - Bartoli, Carlo R.; Demarest, Caitlin T.; Khalpey, Zain; Takayama, Hiroo; Naka, Yoshifumi
Abstract Left ventricular assist device (LVAD) pocket infection is a serious and potentially fatal complication. Not infrequently, the device erodes externally through the thoracoabdominal wall or internally into the peritoneum. In this article, we report two cases to illustrate the presentation and challenges associated with management of LVAD‐pocket infection and wound necrosis. Afterward, we review the current therapeutic strategies for LVAD erosion. doi: 10.1111/jocs.12207 (J Card Surg 2013;28:776–782)